Students' experiences and perceptions of studying for A-Levels: implications for enhancing student resilience. (3rd April 2021) - Nash, Poppy; Naylor, Amanda; Manandhar, Dristi; Stubbs, Joshua; Penten, Philip
ABSTRACT: There is growing concern across Advanced-Level (A-Level) providers and universities that many students are experiencing high levels of stress and physical illness, related to academic and/or social aspects of student life. The impact of academic pressure to 'succeed' is increasingly evident. There is an urgent need to provide appropriate student support. Two studies are reported which investigate students' experiences and perceptions of studying Advanced-Levels in England. By gaining insight into this period of study and the challenges encountered by students, the implications for enhancing student resilience can be better understood. Study One involved participants at four sixth forms in secondary schools in England (n = 805). Study Two comprised a larger-scale study of nine institutions offering A-Level education (secondary school, Sixth Form College and College of Further Education), with 2, 040 Year 12 and Year 13 students participating in the study. In both studies, students completed a bespoke questionnaire which focused on transition to/from A-Level education and student perceptions of resilience. The findings suggest that much more needs to be done in supporting the mental well-being and resilience of students whilst studying for A-Levels. Indeed, the experience of studying for A-Levels was evidently stressful and anxiety-inducing for many of the student participants. This stage of post-secondary education could be seen as the culmination of all the pressures inherent in the present performativity culture of schools. The transition from A-Level study to university can be a very challenging one for a substantial minority of students.